2020
DOI: 10.3390/s20185391
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Robust Multi-Scale Featured Local Binary Pattern for Improved Facial Expression Recognition

Abstract: Compelling facial expression recognition (FER) processes have been utilized in very successful fields like computer vision, robotics, artificial intelligence, and dynamic texture recognition. However, the FER’s critical problem with traditional local binary pattern (LBP) is the loss of neighboring pixels related to different scales that can affect the texture of facial images. To overcome such limitations, this study describes a new extended LBP method to extract feature vectors from images, detecting each ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Shan et al [ 15 ] empirically evaluated facial representation based on a statistical local feature called LBP, experiments had shown that the LBP feature has a better, stable, and robust performance when the input facial images have different forms. To overcome the limitation that traditional LBP can lose the neighboring pixels related to different scales that can affect the texture of facial images, Yasmin et al [ 30 ] proposed a new extended LBP method based on the bitwise “AND” operation of two rotational kernels to extract facial features. In view of satisfactory performance of the LBP operator, the CNNs that integrate advantages of the LBP have been developed [ 41 , 55 , 56 ].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Shan et al [ 15 ] empirically evaluated facial representation based on a statistical local feature called LBP, experiments had shown that the LBP feature has a better, stable, and robust performance when the input facial images have different forms. To overcome the limitation that traditional LBP can lose the neighboring pixels related to different scales that can affect the texture of facial images, Yasmin et al [ 30 ] proposed a new extended LBP method based on the bitwise “AND” operation of two rotational kernels to extract facial features. In view of satisfactory performance of the LBP operator, the CNNs that integrate advantages of the LBP have been developed [ 41 , 55 , 56 ].…”
Section: Related Workmentioning
confidence: 99%
“…Facial expressions can be divided into six basic emotions, namely, anger (An); disgust (Di); fear (Fe); happiness (Ha); sadness (Sa); surprise (Su); and one neutral (Ne) emotion [ 9 ], contempt (Co), was subsequently added as one of the basic emotions [ 10 ]. Recognition of these emotions can be categorized into image-based [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and video-based [ 38 , 39 , 40 , 41 , 42 , 43 ] approaches. Image-based approaches only use information about the static input image to determine the category of facial expression; on the other hand, except when the spatial features extracted from a static image are available, video-based approaches can also use temporal information of a dynamic image sequence to capture the temporal changes of facial appearance when some facial expression occurs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…) is an operator that is used to describe the local texture features of an image [41]. It has the characteristics of multiresolution, invariant gray scale, and rotation; therefore, it is a good measure for image feature extraction, as shown in Figure 3.…”
Section: Local Binary Pattern Histogram Local Binary Pattern (Lbpmentioning
confidence: 99%